Complement C3a Enhances the Phagocytic Activity of B Cells Through C3aR in a Fish - Ma, Zi-You; Liang, Jia-Xin; Li, Wen-Shuo; Sun, Yuan; Wu, Chang-Song; Hu, Ya-Zhen; Li, Jun; Zhang, Yong-An; Zhang, Xu-Jie (Frontiers in Immunology, 2022)
The complement system is an important part of the immune system of teleost fish. Besides, teleost B cells possess both phagocytic activity and adaptive humoral immune function, unlike mammalian B1 cells with phagocytic activity and B2 cells specific to adaptive humoral immunity. However, the cross talk between complement system and phagocytic B cells in teleost fish still requires elucidation. Here, we show that, unlike tetrapods with a single C3 gene, nine C3 genes were identified from the grass carp (Ctenopharyngodon idella) genome, named C3.1-C3.9. Expression analysis revealed that C3.1 is the dominant C3 molecule in grass carp, for its expression was significantly higher than that of the other C3 molecules both at the mRNA and protein levels. The C3a fragment of C3.1 (C3a.1) was determined after the conserved C3 convertase cleavage site. Structural analysis revealed that C3a.1 consists of four α-helixes, with the C-terminal region forming a long α-helix, which is the potential functional region. Interestingly, we found that the recombinant GST-C3a.1 protein and the C-terminal α-helix peptide of C3a.1 both could significantly enhance the phagocytic activity of IgM+ B cells. Further study revealed that the C3a receptor (C3aR) was highly expressed in grass carp IgM+ B cells, and the phagocytosis-stimulating activity of C3a.1 could be dramatically inhibited by the anti-C3aR antibodies, indicating that C3a.1 performed the stimulating function through C3aR on IgM+ B cells. Taken together, our study not only uncovered the novel phagocytosis-stimulating activity of C3a, but also increased our knowledge of the cross talk between complement system and phagocytic B cells in teleost fish.